Pengaruh Aplikasi N, P dan K serta Pupuk Hayati terhadap P-Tersedia, Serapan P, dan Hasil Jagung Manis - Yanuar Euro Andrian; Anni Yuniarti; Rina Devnita (Soilrens, 2021)
Sweet corn is one of the profitable crops with high prospect in Indonesia. Unfornately corn production in Indonesia remained low. This experiment aimed to determine the effect of biofertilizer application along with N, P and K fertilizer Towards phosphor availability, phosphor uptake, and sweet corn yield. The research was conducted at the experimental field of Soil Chemistry and Plant Nutrition, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor from October 2020 until January 2021. The experiment design was Randomized Block Design (RBD) with nine treatments consisted of one control treatment, one N, P and K fertilizer treatment (300 kg/ha Urea, 150 kg/ha SP-36, dan 50 kg KCl), one N, P, and K ¾ + ¾ recommended biofertilizer dose , one dose of N, P, and K ¾ + one recommended biofertilizer dose, one N, P, and ¾ K dose + 1½ recommended biofertilizer dose , one dose of N, P, and one dose of K + ½ recommended biofertilizer dose, one N, P, and one K dose + ¾ recommended biofertilizer dose, one N, P, and one K dose + 1 recommended biofertilizer dose, and one N, P, and one K dose + 1½ recommended biofertilizer dose. The experimental results showed that combination treatments N, P and K fertilizer with biofertilizer has a significant impact on phosphor availability, phosphor uptake, and sweet corn yield. The ¾ N, P and K with one recommended biofertilizer dose, treatment showed the best result on phosphor availability (17,23 ppm), phosphor uptake (0,087 mg/plant), and yield of sweet corn 474,97 g/plant.